2006
DOI: 10.1080/01676830600675392
|View full text |Cite
|
Sign up to set email alerts
|

“Cryoanalgesic Preparation” Before Local Anaesthetic Injection for Lid Surgery

Abstract: The study shows that "cryopreparation" by local ice application immediately prior to local anaesthetic injection reduces the sensitivity to the injection by a significant 24.6%. Thus while all the advantages of good analgesia are obtained from the injection, the distressing discomfort is reduced. This study serves as a pilot, in demonstrating a novel method of pain control for lid surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
35
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 6 publications
(14 reference statements)
2
35
0
Order By: Relevance
“…No attempt was made to use a fixed volume of infiltrate, to disclose the randomisation procedure, to 'blind' the patients to the research question, to control for rate of infusion or to standardise the technique. Our study extends the findings of Goel and colleagues [29], by demonstrating similar benefits prior to abdominal procedures through the use of cooled packs, thereby diminishing the risks associated with topical ice application.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…No attempt was made to use a fixed volume of infiltrate, to disclose the randomisation procedure, to 'blind' the patients to the research question, to control for rate of infusion or to standardise the technique. Our study extends the findings of Goel and colleagues [29], by demonstrating similar benefits prior to abdominal procedures through the use of cooled packs, thereby diminishing the risks associated with topical ice application.…”
Section: Discussionsupporting
confidence: 74%
“…However, that study was not a randomised control trial and Harbet did not support his results with objective pain scores. To the best of our knowledge, the application of preinfiltrative topical ice has only been the subject of one previous randomised trial [29]. This recently published study demonstrated the efficacy of cryo-analgesia prior to eyelid surgery, although the study had a number of methodological flaws.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies support the theory that application of cold decreases nerve conduction, so providing analgesia [13,15,16]. Despite lack of related studies, In a study of 22 patients underwent local lid anaesthetic infiltration, local ice application prior to local anaesthetic injection significantly reduced the pain and discomfort of the injection [17]. Yoon et al, also reported that pretreatment use of ice cubes was effective in reducing pain and discomfort related to intra-dermal skin injection [13].…”
Section: Discussionmentioning
confidence: 88%